Offshore pioneers : Brown & Root and the history of offshore oil and gas - Pratt, Joseph A. (Gulf Pub. Co., 1997)
"Fifty years ago, in November 1947, Brown & Root helped Kerr-McGee build the first out-of-sight-of-land offshore platform that produced oil." "This history puts a human face on the process of technological change. Using the words of many of those who took part in Brown & Root's offshore activities, this book recounts their efforts to find practical ways to recover offshore oil."--Jacket